Mecanismos de resistencia de toxoplasma gondii a fármacos antiparasitarios y su papel en la búsqueda de tratamientos efectivos (2020)
Toxoplasmosis is a parasitic disease caused by the protozoan Toxoplasma gondii. It is one of the most prevalent parasitic infections worldwide and can cause fatal symptoms to immunocompromised patients. Current pharmacologic treatments are associated with adverse effects, hypersensitivity reactions and are not effective against all the life stages of the parasite; therefore, the development of new therapy alternatives is an active field of investigation. One of the problems inside this field is the appearance of strains that are resistant to several drugs used against the parasite. This document presents a review of drug resistance mechanisms found in T. gondii, which were analyzed and compared to find key characteristics that should be present in an ideal molecular target against the parasite. Additionally, a list of metabolic pathways and specific proteins that are currently under investigation is presented, in order to find which molecular targets are the most promising ones in anti-Toxoplasma drug development. The information and considerations gathered here are expected to help focus and guide ongoing pharmacologic investigation towards the most attractive targets, which have a higher probability of success inside the process of drug design and development.